Sex differences and the effects of modified combat regulations on endurance capacity in judo athletes: A meta-analytic approach - Sterkowicz-Przybycien, K.; Fukuda, D. H. (Journal of Human Kinetics, 2016)
Judo requires endurance capacity to recover from its high-intensity intermittent actions. This systematic review aimed to evaluate VO2max and the anaerobic threshold in competitive male and female judo athletes. Twelve eligible studies were chosen for quantitative meta-analysis, including results for 188 male and 159 female athletes. Combined values were calculated and compared by gender prior to and following altered combat regulations in 2003. No significant differences in VO2max were noted following the rule changes, but female athletes` values increased to a level comparable to those reported in male athletes prior to the alterations. VO2max in male judo athletes was higher (54.8±1.9 ml·kg-1·min-1) than in female athletes (48.7±2.2 ml·kg-1·min-1). The effect size of gender was large (d = 1.30) for VO2max and negligible for the anaerobic threshold. Sexual dimorphism exists in VO2max of judo athletes and changes in combat duration did not affect these differences.